1999
DOI: 10.1099/0022-1317-80-2-501
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the geminivirus bean yellow dwarf virus to dicotyledonous hosts involves both virion-sense and complementary-sense genes.

Abstract: Bean yellow dwarf virus (BeYDV) and maize streak virus (MSV) belong to the geminivirus genusMastrevirus and have host ranges confined to dicotyledonous and monocotyledonous species, respectively. To investigate viral determinants of host range specificity, chimeras were constructed by exchanging their coding and non-coding regions. BeYDV chimeras containing MSV ORF V1, ORF V2 or small intergenic region sequences, either individually or in various sequential combinations, replicated and produced virus particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Although no studies have linked the begomovirus AL1 protein to host range (49,52), the reversion of a tomato yellow leaf curl virus C4 mutant in tomato but not in N. benthamiana has been attributed to different host constraints on systemic movement (29). Mastrevirus replication proteins have also been implicated in host adaptation (33). Interestingly, partial reversion of a three-nucleotide mutation in the RepA coding sequence also occurs at 100% frequency during maize streak virus (MSV) infection (67).…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have linked the begomovirus AL1 protein to host range (49,52), the reversion of a tomato yellow leaf curl virus C4 mutant in tomato but not in N. benthamiana has been attributed to different host constraints on systemic movement (29). Mastrevirus replication proteins have also been implicated in host adaptation (33). Interestingly, partial reversion of a three-nucleotide mutation in the RepA coding sequence also occurs at 100% frequency during maize streak virus (MSV) infection (67).…”
Section: Discussionmentioning
confidence: 99%
“…Functional analyses of recombinant genes [9], [10] and genomes [11]–[13] has indicated that a large proportion (and possibly the vast majority) of recombination events between distantly related genomes probably yield defective progeny.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of bacterial [14]–[16] and viral recombination [6], [12], [13], [17] and protein engineering studies utilising DNA-shuffling methodologies [9], [10], [15], [18] have indicated that the probability of a given recombination event being deleterious depends on the modularity of the specific gene(s) or sub-gene module(s) that are transferred and tends to increase with decreasing parental sequence relatedness. This effect is caused, at least in part, by the tendency of recombination to disrupt the networks of genome encoded sequence specific interactions that underpin the biology of all organisms.…”
Section: Introductionmentioning
confidence: 99%
“…With their small genome size, recombinogenic nature, and high mutation rates, geminiviruses have proved to be excellent models for experimental studies of the evolutionary mechanisms of virus emergence and adaptation. Accordingly, various experiments involving geminiviruses - and MSV in particular - have illuminated genetic factors underpinning important evolutionary processes, including the adaptation of these viruses to specific vector species [34] or hosts [35-37], their mutational dynamics [2,3,38-41], and the biochemical and selective factors constraining their adaptation through recombination [37,42-45]. …”
Section: Introductionmentioning
confidence: 99%